Compositing graphene oxide with carbon fibers enables improved dynamical thermomechanical behavior of papers produced at a large scale. (25th March 2023) - Kowiorski, Krystian; Heljak, Marcin; Strojny-Nędza, Agata; Bucholc, Bartosz; Chmielewski, Marcin; Djas, Małgorzata; Kaszyca, Kamil; Zybała, Rafał; Małek, Marcin; Swieszkowski, Wojciech; Chlanda, Adrian
Abstract: This article discusses the morphology and thermomechanical properties of graphene oxide (GO) paper sheets and GO paper composites reinforced with carbon fibers. GO paper was fabricated using GO paste obtained by the condensation of GO aqueous solution synthesized using the Hummers' method. Carbon fibers were implemented to improve the mechanical properties of the pristine GO paper. All the investigated papers were subjected to thermal treatment to check thermo-related morphological and mechanical properties. The results presented in this study allowed for the deeper insight into morphological, structural, and mechanical volume and surface-related properties of pristine GO and GO-based composite materials reinforced with carbon fibers. We showed that there are two important factors that should be taken into consideration for the design and fabrication of GO-based papers. These factors were the concentration of the reinforcing agent and the thermal reduction of the papers. Both factors have influenced the final properties of the resulting GO-based papers. For the first time, it was revealed how the addition of the reinforcing material affects the GO paper thermal expansion coefficient. Graphical abstract: Image 1